Health Utilities Lost and Risk Factors Associated With HPV-induced Diseases in Men and Women: The HPV Italian Collaborative Study Group - Marcellusi, Andrea; Capone, Alessandro; Favato, Giampiero; Mennini, Francesco Saverio; Baio, Gianluca; Haeussler, Katrin; Bononi, Marco (Clinical therapeutics, 2015)
A complete economic evaluation requires accurate data concerning the resources used, outcomes, and utilities (patient’s preferences) to properly value the cost utility of human papillomavirus (HPV) vaccination strategies. This study was designed to measure the utility loss in health states affected by a broad range of HPV-induced pathologies in both sexes in Italy. As a secondary objective, risk factors influencing the viral transmission and development of HPV infections were also investigated. Patients with a diagnosis of several HPV-induced pathologies including atypical squamous cells of undetermined significance (ASC-US), cervical intraepithelial neoplasia (CIN), cervical and anal-colorectal cancer, head and neck squamous cell carcinoma (HNSCC) and anogenital warts (AWs) were evaluated. Utilities, quality of life, and risk factors were elicited using a standardized and computer-guided administration of time trade-off, European Quality of Life 5 Dimensions (EQ-5D), 3 levels, and risk factor questionnaires. Utilities were measured at 6 clinical research centers across Italy. A group of healthy subjects was used as a control. A mean number of 20 healthy subjects was used as a control for each pathology group. Overall, 600 respondents were eligible for analysis: 465 patients (mean [SD] age, 44.0 [16.3] years) and 135 controls (mean [SD] age, 44.0 [13.2] years). With the exception of anal and HNSCC cancer, no statistically significant differences were observed between case and control groups, in terms of either age or quality of life at the time of interview. The patients’ perception of their health condition at baseline was equal to an EQ-5D score of 0.87 (0.22). The mean (SD) value of utilities associated with the HPV-induced pathologies corresponded to 0.83 (0.24), 0.78 (0.27), 0.83 (0.22), 0.81 (0.27), 0.58 (0.31), 0.51 (0.26), and 0.69 (0.30) for ASC-US, AWs, CIN 1 (mild), CIN 2–3 (moderate to severe), cervical cancer, anal cancer and HNSCC, respectively. Utility lost due to AWs was significantly higher in females compared with males (0.71 [0.29] vs 0.83 [0.25]; P = 0.018). Having >5 sexual partners increased the risk of acquiring HPV-induced infections as much as 2.52-fold (P = 0.004), whereas for smoking or the age at start of sexual activity younger than 18 years, the risk increased by ~1.62-fold (P = 0.034). High levels of education were associated with a statistically significant protective effect (P < 0.001). Risk factors and utilities elicited in this study can be used as part of future economic assessments of other HPV vaccination strategies, including an immunization program for preadolescents of both sexes in Italy.